The architectural design of the holy shrines (Al-Academy, 2023)
As an architectural philosophical concept, Islamic architecture cannot be considered arches, doors, domes and lighthouses, since Islamic architecture is based on a structural system of religious, mental, philosophical and logical origins and beliefs shared by the arts, technology and the requirements of the surrounding environment. Rather, the architectural designer's distance from it becomes as if it is for people not from this world, and Islamic architecture is not abbreviated on the heritage side as much as it is a renewed "modern" state, dealing with the concepts of Islam that are valid for every time and place. This can be seen through the mechanisms that produced heritage architecture and what was built on it, which is not a simulation of forms without contents. Islamic architecture is the result of Islamic thought in the areas it reached, as it was logical that the Islamic architectural characteristics were greatly influenced by the beliefs and adopters of the Islamic religion and the scientific renaissance that followed. The difference between one region and another is based, for example, on the factors of climate, weather and the previous architectural cultural heritage in the areas where Islam has reached. For example, the open courtyard is spread in Iraq, the Levant and the Arabian Peninsula, while it disappeared in Turkey and other northern regions that Islam reached as a result of the cold atmosphere in the first and the architectural heritage in the second. There is no doubt that the impact of natural manifestations and their temporal and spatial requirements for architectural structures has had a great role in the search for the truth inherent in their expressive means through knowledge of architectural manifestations in Islamic countries, because the birth of theories and their adoption in the formation of architectural forms is not due to criticism of previous theories. Rather, due to the urgent need to provide a new diversification in forms compatible with the surrounding environmental diversity, and the outcome of the above, the naturalization of constructive relations in architecture and art starts according to the techniques and methods of achievement, which use the expressive and subjective aspect in reference to the exclusion of the natural phenomenon, a feature that has represented the common denominator of architectural genres over the ages. It is the one that strengthened its internal construction in order to find a visual equivalent based on the architectural geometric form used in mosques and holy shrines